2014
DOI: 10.1016/s2214-109x(14)70023-3
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease in adults admitted to hospital in a rural region of coastal Kenya: an analysis of data from linked clinical and demographic surveillance systems

Abstract: SummaryBackgroundEstimates of the burden of disease in adults in sub-Saharan Africa largely rely on models of sparse data. We aimed to measure the burden of disease in adults living in a rural area of coastal Kenya with use of linked clinical and demographic surveillance data.MethodsWe used data from 18 712 adults admitted to Kilifi District Hospital (Kilifi, Kenya) between Jan 1, 2007, and Dec 31, 2012, linked to 790 635 person-years of observation within the Kilifi Health and Demographic Surveillance System,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 36 publications
6
54
0
Order By: Relevance
“…Kenya (population 43.2 million in 2012) is a middle-income country that is marked by a double-burden of communicable and non-communicable diseases (18) and is underrepresented in publications from SSA on HF epidemiology (8). Findings from an economically developing country in the midst of an epidemiologic transition may have local and worldwide relevance for similarly situated countries.…”
Section: Introductionmentioning
confidence: 99%
“…Kenya (population 43.2 million in 2012) is a middle-income country that is marked by a double-burden of communicable and non-communicable diseases (18) and is underrepresented in publications from SSA on HF epidemiology (8). Findings from an economically developing country in the midst of an epidemiologic transition may have local and worldwide relevance for similarly situated countries.…”
Section: Introductionmentioning
confidence: 99%
“…As with children, the incidence of adult hospitalized pneumonia in our population also appeared low compared to rural African settings, though to our knowledge evidence from the region is limited to Kenya [32,33] and the low HIV prevalence in Togo could explain its lower disease burden [29]. Because the project covered the cost of hospitalization and treatment for all enrolled patients, we consider that direct medical costs were unlikely to limit access to care in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Although injury and HIV were not among the main reasons for visiting the health facility, other studies of the same community have shown injury and HIV as the main cause of death for young men and women, respectively 25 . Furthermore, Etyang and colleagues have reported that injuries were the most common cause of admission to Kilifi County Hospital among men, while infectious and parasitic diseases, and pregnancy-related complications were the most common among women 26 . Similarly, a review of medical causes of admission to hospital among adults in Africa reported injuries to be a leading cause of admission for men, while HIV and pregnancy-related disorders were highest among women 27 .…”
Section: Reasons For Facility Visitmentioning
confidence: 99%